HEALTHY LIFESTYLE BEHAVIOR PRACTICES AND PROFESSIONAL QUALITY OF LIFE OF NURSES IN TERTIARY HOSPITAL - Orte, Christian Jay S.; Aggari, Michael I.; Asio, John Mark R.; Tanagon, Hazel D.; Matibag, Ruby S.; Berek, Pius A L; Bautista, Regie A. (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction:The COVID-19 pandemic juxtaposes the different aspects of life in the world. It mainly affects all the fields including the nursing profession and it turns out that this also affects their work-life balance leading to disproportion of the health lifestyle behaviors (HLB) of our nurses. Moreso, studies were conducted about Professional Quality of life (ProQOL) in different variables influences like mental health, empathy, resilience, stress, and caring behaviors but not with HLB. The study aimed to determine the relationship between healthy lifestyle behaviors and professional quality of life of nurses in a tertiary hospital situated in Pampanga. Method: A descriptive-correlational design was used and it employed a purposive sampling technique to gather the participants under the following inclusion criteria: 1) a registered nurse, 2) currently working in tertiary hospital which serves as the study locale, 3) regardless of the age, clinical area and position, and 3) willing to participate. It utilized standardized tools namely: 1) Health Promoting Lifestyle Profile (HPLP II) by Walker, Sechrist, & Pender (1995) and Professional Quality of Life Measure (ProQOL) created by Stamm (2009). Spearman rho was used for its treatment. Result: It revealed that there is a significant relationship between the healthy lifestyle and professional quality of life of the respondents (rs= .245, p value=.036).Conclusion: It was found that healthy lifestyle behaviors are have a direct relationship with professional quality of life among nurses. As they improve their healthy lifestyle behavior practices, it also improves their professional quality of life.